2016
DOI: 10.1002/2016jc011901
|View full text |Cite
|
Sign up to set email alerts
|

Vernal distribution and turnover of dimethylsulfide (DMS) in the surface water of the Yellow Sea

Abstract: The spatial and interannual variations of dimethylsulfide (DMS) and its precursors, dissolved and particulate dimethylsulfoniopropionate (DMSP), were discussed on the basis of field observations in the surface waters of the Yellow Sea during spring 2007. Maxima of dimethylated sulfur compounds and low chlorophyll a concentrations were found in the central southern Yellow Sea, whereas low concentrations of DMS and DMSP were detected at the boundary between the northern and southern parts of the Yellow Sea. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 95 publications
(134 reference statements)
5
7
1
Order By: Relevance
“…Wong et al, 2005). DMSP concentrations (DMSPd: 0.90-53.31 nM; in the surface layer of Bering Sea during our investigation were generally comparable to the surveys of the sub-Arctic and Arctic regions located at the Northeast Atlantic (DMSPd: <1.25- 199 nM; DMSPp: 10.8-280 nM, Malin et al, 1993), but higher than those in the coastal and oceanic surveys ofLi et al (2016b) (DMSPd: 2.13-18.6 nM, DMSPp: 4.14-21.2 nM in the Yellow Sea), and (DMSPd: 1-10 nM; DMSPp: 9-23 nM in the Gulf of Mexico). However, the levels of the dimethylated sulfur compounds we observed were about 255-fold lower than those reported byGalindo et al (2014) in the bottom ice in the Canadian Arctic Archipelago where an DMSP-rich under-ice blooms dominated by pennate diatoms developed.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…Wong et al, 2005). DMSP concentrations (DMSPd: 0.90-53.31 nM; in the surface layer of Bering Sea during our investigation were generally comparable to the surveys of the sub-Arctic and Arctic regions located at the Northeast Atlantic (DMSPd: <1.25- 199 nM; DMSPp: 10.8-280 nM, Malin et al, 1993), but higher than those in the coastal and oceanic surveys ofLi et al (2016b) (DMSPd: 2.13-18.6 nM, DMSPp: 4.14-21.2 nM in the Yellow Sea), and (DMSPd: 1-10 nM; DMSPp: 9-23 nM in the Gulf of Mexico). However, the levels of the dimethylated sulfur compounds we observed were about 255-fold lower than those reported byGalindo et al (2014) in the bottom ice in the Canadian Arctic Archipelago where an DMSP-rich under-ice blooms dominated by pennate diatoms developed.…”
supporting
confidence: 85%
“…DMSPp was positively correlated with Chl a in the surface waters, and in the upper and intermediate waters of the basin ( Figure 6b). This phenomenon was reported in previous studies (e.g., Andreae et al, 1994;Yang et al, 2015), whereas researchers have found poor or no correlations between them in the Ross Sea (DiTullio & Smith, 1995), the Yellow Sea (Li et al, 2016b), and the Mediterranean waters (Sim o et al, 1997;Vila-Costa et al, 2008).…”
Section: Biological Production and Degradation Of Dms And Dmspdsupporting
confidence: 60%
See 2 more Smart Citations
“…AA showed positive relationships with DMSPd in the SYS, which suggests that AA in the SYS is mainly produced by DMSPd degradation rather than the terrestrial inputs. Although phytoplankton plays an important role in controlling 175 the levels of sulfur products, some researchers still found no correlations between Chl a and them in this study area (Li et al, 2016;Yang et al, 2015b) .…”
Section: Incubation Experimentsmentioning
confidence: 69%